2016
DOI: 10.1136/svn-2016-000033
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose intravenous tissue plasminogen activator for acute ischaemic stroke: an alternative or a new standard?

Abstract: BackgroundWith the recent publication of a large clinical trial on the use of a lower dose of intravenous (IV) tissue plasminogen activator (tPA) for acute ischaemic stroke (AIS), the concept of using a different dose has been debated. We intend to review the literature on using a lower dose of IV tPA and gain a better understanding of the impact of different IV doses on the treatment of patients with AIS.MethodsA comprehensive literature search of the related topics in PubMed, EMBASE, Web of Science and MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The difference was that the dose of alteplase was adjusted in one study [18], which was 0.6 mg/kg. Previous studies [22][23][24][25][26] showd that compared with the 0.9 mg/kg dose group, there was no difference in the main efficacy indicators and safety indicators in the low-dose alteplase group. A study showed that starting anti-platelet-aggregation therapy as early as the beginning of intravenous thrombolysis, or as late as 120 min after thrombolytic therapy, which was much earlier than the 24 h recommended by current guidelines, benefited the patients of AIS, but this conclusion needs to be further confirmed by more high-quality studies.…”
Section: Discussionmentioning
confidence: 82%
“…The difference was that the dose of alteplase was adjusted in one study [18], which was 0.6 mg/kg. Previous studies [22][23][24][25][26] showd that compared with the 0.9 mg/kg dose group, there was no difference in the main efficacy indicators and safety indicators in the low-dose alteplase group. A study showed that starting anti-platelet-aggregation therapy as early as the beginning of intravenous thrombolysis, or as late as 120 min after thrombolytic therapy, which was much earlier than the 24 h recommended by current guidelines, benefited the patients of AIS, but this conclusion needs to be further confirmed by more high-quality studies.…”
Section: Discussionmentioning
confidence: 82%
“…These pivotal trials also became the basis for eligibility of patients to receive the thrombolytic therapy along with the mode and dose of medication administration. The alteplase dose is calculated according to the patient's body weight (0.9 mg/kg), with a maximum dose of 90 mg, of which 10% is given as a loading bolus over 1 min and the remainder administered through an intravenous infusion over 1 h. Notably, there are some regions including Japan where a smaller dose of 0.6 mg/kg is utilized owing to concerns for increased complications and bleeding risks in their specific patient populations [18,19]. These regional recommendations have been supported by the results of the ENCHANTED study (Enhanced Control of Hypertension and Thrombolysis Stroke Study) that enrolled 3310 predominantly Asian patients to receive either the standard 0.9 mg/kg or a lower 0.6 mg/kg of IV alteplase within 4.5 h of stroke onset [20].…”
Section: Alteplasementioning
confidence: 99%
“…However, other relevant clinical trials have used different tPA doses. For instance, the ECASS trial 7 used a higher infusion dose of 1.1 mg/kg, while doses as low as 0.3 mg/kg have also been tested 8 . The J-MARS study 9 evaluated the use of 0.6 mg/kg intravenous dose for the treatment of ischaemic stroke and found low levels of ICH (<5%) and relatively high levels of functional outcome at 3 months (>30%).…”
Section: Introductionmentioning
confidence: 99%